2018
DOI: 10.1186/s13099-018-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of human enteric viruses circulating among children with acute gastroenteritis in Valencia, Venezuela, before rotavirus vaccine implementation

Abstract: BackgroundThe role of rotavirus as main etiologic agent of diarrhea has been well documented worldwide, including in Venezuela. However, information about the prevalence of gastrointestinal viruses such as calicivirus, adenovirus and astrovirus is limited and the contribution of other agents as Aichi virus and klassevirus is largely unknown. To explore the etiological spectrum of diarrhea associated with agents other than rotaviruses, 227 stool samples from children under 5 years old with acute gastroenteritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
(74 reference statements)
3
17
2
Order By: Relevance
“…In the present study, adenovirus, astrovirus, and norovirus co-infections with rotavirus were determined. Our results indicated that, unlike other studies, only was rotavirus found co-infecting with other enteroviruses, where no co-infection between adenovirus, astrovirus, and norovirus was detected, whereas reports from South America indicated viral co-infections in samples from patients diagnosed with AGE (2,43,44). In summary, co-infections between enteric viruses are increasing, which represents a serious problem for human health due to the emergence of these viruses in children under fiveyears-old (2, 27, 43-45).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…In the present study, adenovirus, astrovirus, and norovirus co-infections with rotavirus were determined. Our results indicated that, unlike other studies, only was rotavirus found co-infecting with other enteroviruses, where no co-infection between adenovirus, astrovirus, and norovirus was detected, whereas reports from South America indicated viral co-infections in samples from patients diagnosed with AGE (2,43,44). In summary, co-infections between enteric viruses are increasing, which represents a serious problem for human health due to the emergence of these viruses in children under fiveyears-old (2, 27, 43-45).…”
Section: Discussioncontrasting
confidence: 94%
“…Among enterovirus-positive samples, the highest incidence was related to rotavirus, followed by adenovirus, indicating differences from the incidence of enteric viruses worldwide, in which the norovirus incidence was second after that of rotavirus (21,22). Viral co-infections were detected in 14% of the analyzed samples, where rotavirus was detected coinfecting with other detected enteroviruses (2).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Adenoviruses were detected as co-infection viruses in 20.9% (9/43) of the positive samples. According to several studies conducted in Korea, Japan, Albania, and Venezuela, mixed infections of enteric and non-enteric adenoviruses are common and might play a role in acute gastroenteritis [39][40][41][42][43]. The clinical importance of mixed viral infection is an unresolved question.…”
Section: Discussionmentioning
confidence: 99%